Anisotropic fracture resistance of avian eggshell. (October 2020) - Tanaka, Carina B.; Zhou, Yuxuan; Gludovatz, Bernd; Kruzic, Jamie J.
Abstract: In order to understand the fracture toughness anisotropy of avian eggshells, we have investigated eggshells of the emu ( Dromaius novaehollandiae ) whereby the large size (~13 cm × 9.5 cm) enabled the fabrication of beam samples in various orientations. The emu eggshell was found to have a hierarchical microstructure similar to chicken eggshell, with the only significant difference being the absence of a continuous cuticle layer. Emu eggshell was found to have significantly lower strength when samples were tested in the outwards direction ( i.e., a crack initiates on the inside of the shell and propagates towards the outer surface) as compared to the inwards testing direction. Furthermore, samples that were oriented parallel to the egg axis ( i.e., the longitudinal direction) and tested inwards showed higher strength, ~24 MPa, compared to the samples that were made from the latitudinal orientation, ~20 MPa. Independent of orientation, the outwards testing direction resulted in strength values of ~15 MPa. The fracture toughness of the emu eggshell for cracking in the circumferential direction was ~0.3 MPa√m, independent of sample orientation, and this value was comparable to the fracture toughness of chicken eggshell tested in the same orientation. In the radial outwards direction, however, the fracture toughness was ~80% lower (~0.06 MPa√m) than in the circumferential direction. The low fracture toughness for this orientation was associated with the separation of the highly oriented calcite crystals in the mammillary cone layer of the eggshell structure which is easier compared to calcite crystal fracture. The large anisotropy in fracture toughness is thought to allow for easy escape of the chick while simultaneously protecting the embryo during development. Graphical abstract: Image 1 Highlights: Avian eggshell has anisotropic strength and fracture behavior. Microstructure is similar among avian eggshells. Fracture toughness of emu eggshell is similar to chicken eggshell. Radial fracture toughness is ~20% of circumferential fracture toughness.